Do isolated trees encourage arboreal ant foraging at ground level? Quantification of ant activity and the influence of season, in Veracruz, Mexico - Majer, Jonathan; Gove, Aaron (2006)
Removal rates of dead fruit flies were used in a tropical dry grassland of Veracruz, Mexico to indicate whether foraging by ants would be higher under isolated trees than in open grassland, and if foraging rates would differ seasonally. It was hypothesised that foraging rates would be higher under trees during the dry season, when arboreal food resources were minimal, and when arboreal ants were inclined to forage at ground-level. However, arboreal ant species were more abundant in pitfall traps beneath isolated trees during the wet season months of May and July and they never made up more than 3% of ants sampled at ground-level. Neither the presence of trees nor the dry season increased bait removal rate; removal rate on the ground was significantly higher in the wet season and did not vary with habitat type.